Oxytocin and bone quality in the femoral neck of rats in periestropause - Fernandes, Fernanda [UNESP]; Stringhetta-Garcia, Camila Tami [UNESP]; Peres-Ueno, Melise Jacon [UNESP]; Fernandes, Fabiana [UNESP]; Nicola, Angela Cristina de [UNESP]; Castoldi, Robson Chacon [UNESP]; Ozaki, Guilherme [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Ervolino, Edilson [UNESP]; Dornelles, Rita Cássia Menegati [UNESP] (Springer Nature, 2020)
The objective of this study is to identify whether oxytocin (OT) contributes to the reduction of osteopenia in the femoral neck of rats in periestropause. Animals in irregular estrous cycles received two NaCl injections (0.15 mol/L) or OT (134 μg/kg) over a 12-h interval, and after thirty-five days without treatments, the biological sample collection was performed. The oxytocin group (Ot) demonstrated the highest enzymatic activity of alkaline phosphatase (p = 0.0138), lowest enzymatic activity of tartrate-resistant acid phosphatase (p = 0.0045), higher percentage of compact bone (p = 0.0359), cortical expression of runt-related transcription factor 2 (p = 0.0101), osterix (p = 0.0101), bone morphogenetic protein-2/4 (p = 0.0101) and periostin (p = 0.0455). Furthermore, the mineral-to-matrix ratio (ν1PO4/Proline) was higher and type-B carbonate substitution (CO3/ν1PO4) was lower (p = 0.0008 and 0.0303) in Ot group. The Ot showed higher areal bone mineral density (p = 0.0050), cortical bone area (p = 0.0416), polar moment of inertia, maximum, minimum (p = 0.0480, 0.0480, 0.0035), bone volume fraction (p = 0.0166), connectivity density (p < 0.0001), maximal load (p = 0.0003) and bone stiffness (p = 0.0145). In Ot percentage of cortical pores (p = 0.0102) and trabecular number (p = 0.0088) was lower. The results evidence action of OT in the reduction of osteopenia, suggesting that it is a promising anabolic strategy for the prevention of primary osteoporosis during the periestropause period.